Influence of material nonlinearity on the durability of piezoelectric energy harvesters using macro fibre composite - Zhang, Raynald Yong Quan (2015)
Ambient vibration energy has been heavily considered as a source for powering wireless sensor nodes and replace batteries to save operational cost. Previous studies have looked into optimising power output to fit commercial needs as well as raising bandwidth to have high power output over a wider range of frequencies. In this report, the issue of piezoelectric harvester (PEH) durability will be studied so as to aid the design of a long lasting and practical PEH. Macro Fibre Composite (MFC), which is used as piezoelectric material in this study, will be tested for voltage output, displacement and strain under various excitation accelerations in the linear and nonlinear range. The tests also involve short and long cyclic loadings to fully test the durability of the MFC. Experimental results have suggested that MFC running at nonlinear range produced very inconsistent and unpredictable results which may be unsuitable for practical implementation, whereas running in linear range produced consistent and stable power output.